2021
DOI: 10.1097/md.0000000000025487
|View full text |Cite
|
Sign up to set email alerts
|

The association between 5, 10 – methylenetetrahydrofolate reductase and the risk of unexplained recurrent pregnancy loss in China

Abstract: Backgroud: To analyze the correlation between gene polymorphisms of 5,10- methylenetetrahydrofolate reductase (MTHFR) and risk of unexplained recurrent pregnancy loss (URPL) in Chinese women. Methods: Eligible studies were searched in Pubmed, Embase, Web of Science, Wanfang, and China National Knowledge Infrastructure (CNKI) databases. Established inclusion criteria were used to screening articles, subsequently evaluate the quality of the included studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…A meta-analysis by Du et al [110] suggested that there were some differences in the association between MTHFR C677T polymorphism and RSA, especially in the Asian population, but no significant correlation was found between A1298C and RSA. A meta-analysis by Wang et al [111], which analyzed research conducted only in Chinese women, showed that the MTHFR 677T allele, 677TT genotype, and MTHFR 1298CC genotype were all related to URSA.…”
Section: Mthfr and Mtrrmentioning
confidence: 99%
“…A meta-analysis by Du et al [110] suggested that there were some differences in the association between MTHFR C677T polymorphism and RSA, especially in the Asian population, but no significant correlation was found between A1298C and RSA. A meta-analysis by Wang et al [111], which analyzed research conducted only in Chinese women, showed that the MTHFR 677T allele, 677TT genotype, and MTHFR 1298CC genotype were all related to URSA.…”
Section: Mthfr and Mtrrmentioning
confidence: 99%
“…MTHFR gene variants have been correlated with the increased risk of neural tube [11,12] and congenital heart defects [13,14] as well as recurrent pregnancy losses [3,15,16]. Interestingly, folic acid supplementation has been reported as being potentially effective in reducing the risk of such conditions [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Слід зазначити, що результати досліджень щодо вивчення впливу поліморфних варіантів фолатного циклу у жінок з РВВ неуточненого генезу є досить суперечливими, але доведено, що призначення фолатів у формі монотерапії або у комплексі з іншими вітамінами та мікроелементами на етапі підготовки до вагітності та під час виношування значно знижує ризик невиношування та втрати вагітності, а отже, є важливою профілактикою вад розвитку нервової системи плода та розладів аутистичного спектра у новонароджених і дітей [15][16][17][18].…”
unclassified